2010
DOI: 10.1063/1.3437632
|View full text |Cite
|
Sign up to set email alerts
|

Strain and crystal defects in thin AlN/GaN structures on (0001) SiC

Abstract: Oxygen induced strain field homogenization in AlN nucleation layers and its impact on GaN grown by metal organic vapor phase epitaxy on sapphire: An x-ray diffraction study High-resolution x-ray diffraction was used to compare strain relaxation and defect populations in thin GaN/AlN heterostructures ͑total thickness Ϸ480 nm͒ grown on ͑0001͒ SiC using metalorganic chemical vapor deposition ͑MOCVD͒ and hydride vapor epitaxy ͑HVPE͒ techniques. The results of high-resolution x-ray diffraction measurements ͑rocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…Other experiments reporting conductance enhancement attribute the increase to a strengthening of the bonds at the boundaries [15][16][17]. Thermal interface engineering can be critical to many technologies like integrated circuits [3], phase change memory [18] or high power electronics [19]. A systematic and microscopic understanding of the bridging properties of an interfacial layer would go a long way towards that goal.…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments reporting conductance enhancement attribute the increase to a strengthening of the bonds at the boundaries [15][16][17]. Thermal interface engineering can be critical to many technologies like integrated circuits [3], phase change memory [18] or high power electronics [19]. A systematic and microscopic understanding of the bridging properties of an interfacial layer would go a long way towards that goal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the epitaxial thin films under lower deposition rates, the elastic strain in the GaN layers were entirely relaxed at the initial stages of the epitaxial growth yielding nearly similar densities of TDs in layer volume. Therefore, under higher growth rate a mass of TDs could relaxes the more tensile stress [28]. The present results demonstrated that the chamber height emphasize the importance of this parameter for the accommodation of elastic strain and crystalline quality in the epitaxial layers and the dynamics of atom incorporation into a crystal lattice at the growth.…”
Section: Resultsmentioning
confidence: 70%
“…The RHEED pattern for nucleation layer indicates the morphology of the initial annealed growth is smooth, allowing the subsequent growth of a high quality epilayer. 23,26,28,29 The creation of closed dislocation loops in the volume of the layer, just above the interface, is a final stage of defects creation process. 4(b)] yields values of $1.7 Â 10 5 cm À2 and 1.6 Â 10 7 cm À2 , respectively.…”
Section: X-ray Diffraction Characterizationmentioning
confidence: 99%
“…4(b)] yields values of $1.7 Â 10 5 cm À2 and 1.6 Â 10 7 cm À2 , respectively. 22,23,28,29 The created closed dislocation loops rise up, following the growth front with the lag, specified by growth conditions and elastic properties of epitaxial layer. 26 The narrow width of the central x RC peak correlates with the crystalline perfection of ZnO layer, but not directly, real more complicated situation is described below.…”
Section: X-ray Diffraction Characterizationmentioning
confidence: 99%